AB1210-HPR Mendelian randomization analysis indicates serum urate has a conditional causal effect on serum creatinine and renal function. (15th June 2017) - Liu, J; Zhang, H; Dong, Z; Zhou, J; Ma, Y; Li, Y; Qian, Q; Yang, Y; Wang, X; Zou, H; Jin, L; Wang, J
Abstract : Background: Uric acid, the weak organic acid and the end product of purine nucleotide degradation, is excreted predominantly by the proximal tubules [1]. Although large numbers of epidemiological, molecular and animal studies have focused on various pathogenic effects of serum uric acid, inclding chronic kidney disease (CKD), metabolic syndrome, and coronary artery disease [2], whether the serum uric acid is an independent risk factor or has causal impact on serum creatinine (SCr) and renal function remains unclear. Objectives: We aim to study the effect of serum uric acid on renal function by applying the method of Mendelian randomization. Methods: The study was represented by estimated glomerular filtration rate (eGFR) with potential confounding factors in 3, 734 Chinese subjects. Four genetic variants of uric acid transporter genes ( rs1481012 [ABCG2], rs16890979 [SLC2A9], rs2231137 [ABCG2] and rs3799352 (SLC17A1] ) were selected for this study as they had highest correlation with serum uric acid in Chinese population in our previous study. In this research, serum uric acid was selected as exposure, genetic risk score of uric acid transporters was selected as instrumental variable, and SCr and eGFR were selected as the outcomes. Results: 1) The results of the analysis showed that increased serum uric acid has a causal effect on reducing estimated glomerular filtration rate in both female population and the subjects who were under 65 years old. Because of protective effects on renal function of ovarian hormones such as estrogen, we postulated that estrogen might be the cause leading to the difference between men and women. 2) We also found that increased serum uric acid led to the damage of renal function in the subjects with normal eGFR value. 3) In addition, the serum uric acid was a risk factor to renal function in the subjects with relative high level of fasting glucose or who were smoking currently. Because of metabolic defects in people affected by diabetes, renal glucose reabsorption was increased, thus further sustaining hyperglycemia in patients. Conclusions: Serum urate has causal effects on renal dysfunction in either female or individuals of under 65, or normal eGFR, or high level of fasting glucose, or current smokers. References: Pasalic D, Marinkovic N, Feher-Turkovic L. Biochem Medica 2012;22(1):63–75. Sakhaee K. J Nephrol 2014;27(3):241–5. Acknowledgements: National Natural Science Foundation of China (31521003), Science and Technology Committee of Shanghai Municipality (11DJ1400102), International S&T Cooperation Program of China (2013DFA30870), Ministry of Science and Technology (2011BAI09B00), 111 Project (B13016), and Program for 2012 Outstanding Medical Academic Leader for Hejian Zou. Computational support was provided by the High-End Computing Center located at Fudan University. Disclosure of Interest: None declared